Surface roughness and hardness of yttria stabilized zirconia (Y-TZP) after 10 years of simulated brushing - Candido, Lucas Miguel [UNESP]; Fais, Laiza Maria Grassi [UNESP]; Reis, José Mauricio dos Santos Nunes [UNESP]; Pinelli, Ligia Antunes Pereira [UNESP] (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
Introduction: The Y-TZP zirconia used for prosthetic infrastructure, in some clinical situations, can be exposed to the oral environment. In these situations, a polished surface without changes is extremely important. Objective: The aim of this study was to evaluate the mean roughness (Ra) and Vickers hardness of Y-TZP zirconia (Lava™) after simulating ten years of brushing. Material and method: Thirty-six Y-TZP bar-shaped specimens (20mm X 4mm X 1.2mm) were divided into three groups: storage in distilled water (DW, n=12, control); brushing with distilled water (BDW, n=12) and brushing with distilled water and fluoride toothpaste (BFT, n=12). Brushing was performed using a brushing machine with a soft-bristled toothbrush, simulating 10 years of brushing (878.400 cycles, 100gf). The mean roughness (Ra in μm) and Vickers hardness (VHN) of all specimens were measured twice: before and after the experimental treatment, in profilometer and microhardness tester (500gf, 30 seconds), respectively. Data were analyzed using the two-way ANOVA test (α = 0.05). Result: The interaction between groups was not significant for roughness (p = 0.701) nor for hardness (p = 0.928). The final averages for Ra (μm) were equal to: DW - 0.63; BDW - 0.64; and, BFT - 0.68. The final averages for Vickers hardness (VHN) were: DW - 1301.16; BDW - 1316.60; and, BFT - 1299.58. Conclusion: It was concluded that the brushing with distilled or fluoridated toothpaste was not able to change the roughness and hardness of Y-TZP zirconia used in this study.

Introdução: A zircônia estabilizada por ítria (Y-TZP) utilizada para infraestruturas protéticas pode, em algumas situações clínicas, ficar exposta ao meio bucal, e nessas situações, uma superfície sem alterações e polida é extremamente importante. Objetivo: Assim, este estudo avaliou a rugosidade média (Ra) e a dureza Vickers da zircônia Lava™ após simulação de dez anos de escovação. Material e método: Foram confeccionados 36 espécimes (20mm X 4mm X 1,2mm), divididos em três grupos: armazenamento em água destilada (AD, n=12, controle), escovação com água destilada (EAD, n=12) e escovação com água destilada e dentifrício fluoretado (EDF, n=12). A escovação foi realizada em máquina de escovação simulando 10 anos (878.400 ciclos, lOOgf) com escova dental macia. A rugosidade média (Ra, em μm) e a dureza Vickers (VHN) de todos os corpos-de-prova foram mensuradas em dois momentos: antes e após o tratamento experimental, em rugosímetro e microdurômetro (500gf, 30 segundos), respectivamente. Os dados foram analisados por meio do teste two-way ANOVA (α=0,05). Resultado: A interação entre os grupos não foi significativa tanto para a rugosidade (p=0,701) quanto para a dureza (p=0,928), sendo as médias finais de Ra (μm) iguais a: AD - 0,63; EAD - 0,64 e EDF - 0,68 e as de dureza Vickers (VHN) iguais a: AD - 1301,16; EAD - 1316,60 e EDF - 1299,58. Conclusão: Concluiu-se que o procedimento de escovação com água destilada ou com dentifrício fluoretado não foi capaz de alterar a rugosidade e a dureza da zircônia Y-TZP utilizada neste estudo.
Avaliação da rugosidade e dureza da zircônia Y-TZP após simulação de 10 anos de escovação
Keywords: Hardness; Toothbrushing; Ceramics; Dureza; Escovação dentária; Cerâmica